2016
DOI: 10.1071/an14731
|View full text |Cite
|
Sign up to set email alerts
|

Production and physiological effects of perennial ryegrass alkaloids under thermoneutral conditions in Merinos

Abstract: A confined feeding study was conducted to compare the production and physiological effects of feeding three doses of wild-type perennial ryegrass alkaloids via whole seed to Merino sheep housed under thermoneutral conditions (21°C, 50% relative humidity). Eighteen Merino ewe weaners (16 months; initial bodyweight 47 ± 1.94 kg) were offered Nil, Low (50 µg/kg liveweight ergovaline, 22 µg/kg liveweight lolitrem B) or High (100 µg/kg liveweight ergovaline, 44 µg/kg liveweight lolitrem B) doses of alkaloids for 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 30 publications
2
10
2
Order By: Relevance
“…A key finding from the present study was that DMI was decreased by 22% in response to consumption of rye grass seed that contained moderate levels of endophyte alkaloids. A reduction in DMI due to alkaloid consumption has been reported in previous studies by the same authors when thermoneutral and moderate heat conditions were used for the same period of time [ 14 , 16 ]. Furthermore, this finding is consistent with a previous study which found feed intake decreased in cattle fed endophyte infected tall fescue (containing ergovaline) under 32 °C ambient temperature conditions [ 3 ].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…A key finding from the present study was that DMI was decreased by 22% in response to consumption of rye grass seed that contained moderate levels of endophyte alkaloids. A reduction in DMI due to alkaloid consumption has been reported in previous studies by the same authors when thermoneutral and moderate heat conditions were used for the same period of time [ 14 , 16 ]. Furthermore, this finding is consistent with a previous study which found feed intake decreased in cattle fed endophyte infected tall fescue (containing ergovaline) under 32 °C ambient temperature conditions [ 3 ].…”
Section: Discussionsupporting
confidence: 68%
“…A previous study using goats found only a small percentage (1.6%) of whole perennial ryegrass seed passes through to the faeces [ 15 ] so seed was fed whole. Additionally, previous studies by the authors have found feeding seed whole produces consistent PRGT effects [ 14 , 16 ]. Lolitrem B levels are higher than ergovaline in plant tissue [ 17 ], in the current study seed was fed which contained lower levels of lolitrem B compared to ergovaline.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations